Hypertrophic Cardiomyopathy in 2012 - Carolyn Y. Ho (2012)
A healthy 32- year-old man presents for evaluation of exertional dyspnea and syncope.A murmur is noted, and echocardiography reveals marked septal hypertrophy with a resting left ventricular outflow tract gradient of 68 mm Hg (online-only Data Supplement Movie I and Figure I).His father died of an MI at 38 years of age, and his paternal uncle died as the driver in a single-car accident at 30 years of age.His younger brother is thought to have athlete's heart (Figure 1A).After discussing his diagnosis of hypertrophic cardiomyopathy and implications for his family, he asks, "What will happen to my kids?Will I be able to feel well enough to exercise again?"